Clinical drug data /Philip O. Anderson, James E. Knoben, William G. Troutman. - Anderson, Philip O.,Editors
Rev. ed. of: Family practice board review / [editor-in-chief] William A. Schwer ; [associate editors] Scott H. Plantz, Gillian Emblad. 3rd ed. c2006.